A Core Reduction Experiment Finds No Effect of Original Stone Size and Reduction Intensity on Flake Debris Size Distribution. Issue 3 (July 2016) - Lin, Sam C.; Pop, Cornel M.; Dibble, Harold L.; Archer, Will; Desta, Dawit; Weiss, Marcel; McPherron, Shannon P.
Abstract : Studies have long noted the influence of stone package size and reduction intensity on lithic assemblage composition, particularly in the form of flake size distributions. However, it remains difficult to distinguish objectively the effect of either factor in archaeological contexts without controlling for the variation in one of the two variables. Here we report on an experimental study designed to test the null hypotheses that original stone size and reduction intensity have no impact on the size distribution of lithic flake debris produced during core reduction. Results indicate statistically significant influence from original stone size but not reduction intensity, although the effects from the former are low enough to be considered trivial. In reviewing a sequence of archaeological assemblages from a Middle Paleolithic site, all exhibit an excess of smallsized materials in comparison to the experimental data. When exceptionally high frequencies of the smaller size classes occur, taphonomic processes are clearly responsible.